2023
DOI: 10.3390/nano13061001
|View full text |Cite
|
Sign up to set email alerts
|

Nanotextured CeO2−SnO2 Composite: Efficient Photocatalytic, Antibacterial, and Energy Storage Fibers

Abstract: Bacterial infections remain a serious and pervasive threat to human health. Bacterial antibiotic resistance, in particular, lowers treatment efficacy and increases mortality. The development of nanomaterials has made it possible to address issues in the biomedical, energy storage, and environmental fields. This paper reports the successful synthesis of CeO2−SnO2 composite nanofibers via an electrospinning method using polyacrylonitrile polymer. Scanning and transmission electron microscopy assessments showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 77 publications
(84 reference statements)
0
2
0
Order By: Relevance
“…Phospholipids are major constituents of the bacterial membrane, and they contain reactive phosphoryl groups next to unmodified lipid carboxyl groups, both of which can interact with metal cations at a neutral and alkaline pH. Significantly, the composition of bacterial phospholipids varies between species, and the interaction with metal is mostly determined by the lipid's outwardly facing polar head group, which is particularly susceptible to perturbations [4,68]. Nevertheless, the metal ions possess various fascinating chemical and physical characteristics, which have a substantial impact on the antibacterial effect of the applied compounds (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Phospholipids are major constituents of the bacterial membrane, and they contain reactive phosphoryl groups next to unmodified lipid carboxyl groups, both of which can interact with metal cations at a neutral and alkaline pH. Significantly, the composition of bacterial phospholipids varies between species, and the interaction with metal is mostly determined by the lipid's outwardly facing polar head group, which is particularly susceptible to perturbations [4,68]. Nevertheless, the metal ions possess various fascinating chemical and physical characteristics, which have a substantial impact on the antibacterial effect of the applied compounds (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Concurrently, photogenerated holes (h + ) are created in the valence band, and under the influence of the internal electric field, photogenerated electrons and holes move separately towards CeO . Additionally, the valence band potential (E VB ) of 50% SC (2.61 eV) is higher (more positive) than the potential for the reaction of valence band holes (h + ) with OH − that leads to the formation of •OH (OH − /•OH 1.99 [57][58][59][60], suggesting that some valence band holes have sufficient oxidative power to oxidize OH − to •OH radicals, following the reaction OH − + h + → •OH. From experiments with active species, it is evident that •O 2 − and •OH play a secondary role in the photodegradation of MB, indicating that there are more unreacted h + species.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Pop et al [54] showed antibacterial activity of CeO2 NPs in relatively low concentrations against two Gram-positive and three Gramnegative bacteria by using the microdilution method. Also, the CeO2−SnO2 nanofibers prepared by Algethami et al [55] demonstrated higher antimicrobial activity than simply The results demonstrated that the antibacterial activity of the hybrid nanomaterial was improved by over three times compared to the system without the antibiotic. The antibacterial performance of the hybrid was due to the triple synergistic effect of GO, AgNPs, and sulfadiazine: bacterial capping, puncture, and inhibition [63].…”
Section: Medical Application: Nanomaterials Against Multi-drug-resist...mentioning
confidence: 96%
“…Furthermore, in recent years, the synthesis of semiconductors materials, in particular CeO 2 NPs, has also received attention due to its diverse properties. CeO 2 NPs can be prepared by wet-chemical synthesis, starting from cerium nitrate and oxalic acid, and applying a thermal treatment after the precipitation [55].…”
Section: Synthesis Of Metal Nanoparticles (Ag Cu Zn Ce)mentioning
confidence: 99%